Smart City Concept of Selected Cities in the Czech Republic - Hruška, Roman; Kučera, Tomáš; Hyršlová, Jaroslava; Machalík, Stanislav; Chocholáč, Jan; Sommerauerová, Dana (Kaunas University of Technology, 2019)
The article deals with Smart City concepts and strategies of selected cities in the Czech Republic. The concept of Smart City has become a point of interest in scientific publications and in public sector over the past ten years. It is a concept of applying sustainable development of cities principles based on the use of modern technologies to improve quality of life and make governance more efficient. This concept is widely used in the field of transport, which can be more effectively addressed by using appropriate information and communication technologies. The article presents an approach to this issue in the Czech Republic with a focus on recommendations and methodologies provided by the Ministry of Regional Development. The concepts and strategies of selected cities are analysed and then compared, with a particular focus on transport in the context of recommendations and methodologies.
Smart City koncept vybraných měst v České republice
Keywords: sustainable urban mobility plans; Smart City concept; sustainable development; plány udržitelné městské mobility; Smart City koncept; udržitelný rozvoj